2017
DOI: 10.1371/journal.pone.0170810
|View full text |Cite
|
Sign up to set email alerts
|

Validity of a New Quantitative Evaluation Method that Uses the Depth of the Surface Imprint as an Indicator for Pitting Edema

Abstract: This study examined the validity of a practical evaluation method for pitting edema by comparing it to other methods, including circumference measurements and ultrasound image measurements. Fifty-one patients (102 legs) from a convalescent ward in Maruyama Hospital were recruited for study 1, and 47 patients (94 legs) from a convalescent ward in Morinaga Hospital were recruited for study 2. The relationship between the depth of the surface imprint and circumferential measurements, as well as the relationship b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…First, regarding the soft tissue thickness that was observed to have a negative correlation with PRT, soft tissue thickness is primarily an indicator of the degree of oedema. 16 Therefore, the results of this study suggest that the more severe the oedema, the shorter the PRT. Previous studies have reported a correlation between the visual extent of oedema and hypoalbuminaemia, 15 suggesting a high likelihood of relationships among soft tissue thickness, PRT and serum albumin levels.…”
Section: Discussionmentioning
confidence: 67%
“…First, regarding the soft tissue thickness that was observed to have a negative correlation with PRT, soft tissue thickness is primarily an indicator of the degree of oedema. 16 Therefore, the results of this study suggest that the more severe the oedema, the shorter the PRT. Previous studies have reported a correlation between the visual extent of oedema and hypoalbuminaemia, 15 suggesting a high likelihood of relationships among soft tissue thickness, PRT and serum albumin levels.…”
Section: Discussionmentioning
confidence: 67%
“…A recent bioimpedance simulation study was published and concluded that future research is warranted to determine the feasibility of the method [ 3 ]. Another study tested the relationship between surface imprint and circumferential measurements as a potential evaluation method for edema but found there to be no significant relationship [ 6 ]. Measuring the circumference of the leg at a single point by using a device such as the Leg-O-Meter has been shown to be reproducible but is only helpful for estimating the volume of the lower limb at the location where the circumference was measured.…”
Section: Discussionmentioning
confidence: 99%
“…Patients treated with liposuction for LEL between September 1993 and May 2017 at the Department of Plastic and Reconstructive Surgery, Skåne University Hospital, Malmö, Sweden were included in this study. The inclusion criteria for the study were unilateral primary and secondary lymphedema with a 10% greater volume in the affected leg than in the contralateral leg; conservative treatment alone not leading to satisfactory reduction; edema with no or minimal pitting (<6-7 mm) [42][43][44] due to fat deposition; and a positive attitude toward continuous use of garments after liposuction. The exclusion criteria were bilateral lymphedema, active cancer, wounds, or ongoing infection.…”
Section: Patientsmentioning
confidence: 99%